Síntese e caracterização de nanopartículas de Cu-ZnO e sua utilização no revestimento de superfícies de titânio por deposição eletroforética - Gênier, Francielli Silva (2017)
The majority of metallic implant failures is due to body rejection to the material’s surface and to postoperative infections. Therefore, preventing bacterial growth on these materials and simultaneously contributing to their body adaptation are the main goals of recent researches on nanomedicine. As a way to reach these objectives, coating metallic prosthesis with nanoparticles represents a viable alternative to traditional treatment methods such as antibiotic administration, whose efficacy decreases as antibiotic-resistant strains of bacteria rise. The present work presentes the use of cooper doped zinc oxide nanoparticles (Cu-ZnO) to coat titanium surfaces, a commonly used material in medical devices, by electrophoretic deposition. These nanoparticles were chosen due their antibacterial characteristics, as presented on recent publications. Through microscopy (SEM and TEM), spectroscopy (EDS), and X-ray diffraction (XRD), the format and composition of the nanoparticles was confirmed as well as their crystallite size (228.24 nm) and lattice parameters. This material was suspended and deposited by electrophoresis on titanium plates for 1 minute under voltages between 100 and 180 V in order to obtain the best deposition condition, which was 160 V. The pH and conductivity of the suspension was also evaluated before and after the EPD. The EDS results confirmed the presence of the nanomaterial in the deposit. SEM images confirmed the increased surface roughness after electrophoretic deposition. Hence, this work’s goal was to explore a new potencial coatings process for artificial implants, in the way of contributing to the nanotechnology research field and its applications on medicine.